Static, dynamic and fatigue behavior of newly designed stem shapes for hip prosthesis using finite element analysis - Zafer Senalp, A.; Kayabasi, Oguz; Kurtaran, Hasan (Elsevier Sci Ltd, 2007)
Forces applied to the implant due to human activity generate dynamic stresses varying in time and resulting in the fatigue failure of implant material. Therefore, it is important to ensure the hip prostheses against static, dynamic and fatigue failure. Finite element method has been used in orthopedic biomechanics as an important tool in the design and analysis of total joint replacements and other orthopedic devices. In this study, four stem shapes of varying curvatures for hip prosthesis were modeled. Static, dynamic and fatigue behavior of these designed stem shapes were analyzed using commercial finite element analysis code ANSYS. Static analyses were conducted under body load. Dynamic analyses were performed under walking load. Pro/Engineer was used for CAD modeling of the stem shapes. Fatigue behavior of stem shapes was predicted using ANSYS Workbench software. Performance of the stem shapes was investigated for Ti-6Al-4V and cobalt-chromium metal materials and compared with that of a commonly used stem shape developed by Charnley. Published by Elsevier Ltd.
Keywords: femur; implant; stem; fatigue; dynamic analysis; finite element method